STRATEGI PENCEGAHAN ILLEGAL LOGGING DI KABUPATEN ROKAN HILIR (STUDI KASUS POLISI RESORT KABUPATEN ROKAN HILIR) - Zawindra, Haldi; Tutrianto, Rio (UIR PRESS, 2022)
Forest was a green area whic is in there are plants or trees and anothe diversity of life related to the natural ecosystem, forest utilization and that result was a reasonable do with exploitation. But be a problem when forest result do with overexploitation, whic one was a illegal logging procces cutting down trees that are used as wood and invalid. Like happened on Rokan Hilir district, this research do in Rokan Hilir jusdriction with studying prevention strategy to illegal logging activity. This reseach do with qualitative and desriptive method also reinforced by crime prevention theory meaning to solve that problem in this research, some of the poduce that action taken by Rokan Hilir police in this crime prevention.